2021
DOI: 10.36787/jti.v15i2.584
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Kombinasi Kitosan dan Ampas Kopi sebagai Adsorben Alami dalam Menurunkan Konsentrasi Arsen Pada Limbah Cair PT PXI

Abstract: Abstrak PXI adalah salah satu perusahaan di Kabupaten Bekasi yang bergerak di bidang jasa layanan laboratorium. Dalam menjalankan kegiatannya, PXI menghasilkan logam arsen ke lingkungan. Keberadaan arsen di dalam air limbah PXI harus segera diselesaikan agar tidak mencemari lingkungan dan membahayakan kehidupan manusia. Metode yang digunakan dalam penelitian ini adalah metode eksperimen dan deskriptif kuantitatif berdasarkan data hasil laboratorium menggunakan instrumen FT-IR, SEM EDX dan AAS. Tahapan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The Research procedure in this study follows the flowchart as presented in Figure 1. The research process from stages 1 to 3 has been carried out in 2021 (Nurhidayanti et al, 2021). The operational conditions employed included pH control, mass variation ranging from 0.6 to 1.4 grams, activated carbon particle size of 160 mesh, initial lead concentration of 1.02 mg/L, stirring speed of 100 rpm, contact time spanning from 5 to 25 minutes, and a temperature range of 25 to 55°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Research procedure in this study follows the flowchart as presented in Figure 1. The research process from stages 1 to 3 has been carried out in 2021 (Nurhidayanti et al, 2021). The operational conditions employed included pH control, mass variation ranging from 0.6 to 1.4 grams, activated carbon particle size of 160 mesh, initial lead concentration of 1.02 mg/L, stirring speed of 100 rpm, contact time spanning from 5 to 25 minutes, and a temperature range of 25 to 55°C.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated that the reduction of lead concentration in industrial wastewater using natural chitosan and activated carbon from coffee grounds as sorbents resulted in a reduction of 90.86%, yielding a final concentration of 0.09 mg/L (Nurhidayanti, Ilyas, & Suwazan, 2021). Previous research has explored the isothermal model and reaction kinetics of metallic arsenic reduction (Nurhidayanti & Nugraha, 2022), as well as the reaction kinetic analysis and adsorption isotherms of chicken egg shells, membranes, and synthetic dyes (Hevira & Gampito, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research results showed that the effectiveness of using natural adsorbents from chitosan and coffee grounds activated carbon in reducing cadmium concentrations in industrial wastewater was 90.86% with a final concentration of 0.07 mg/L (Nurhidayanti et al, 2021). Previously, the isotherm model and kinetics of arsenic metal in reducing arsenic metal (Nurhidayanti & Nugraha, 2022) , kinetic analysis and adsorption isotherm of chicken egg shells and membranes against synthetic dyes (Hevira & Gampito, 2022), kinetic analysis and adsorption isotherm of cadmium onto microalgae Parachlorella sp (Dirbaz & Roosta, 2018) had been studied .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the isotherm model and kinetics of arsenic metal in reducing arsenic metal (Nurhidayanti & Nugraha, 2022) , kinetic analysis and adsorption isotherm of chicken egg shells and membranes against synthetic dyes (Hevira & Gampito, 2022), kinetic analysis and adsorption isotherm of cadmium onto microalgae Parachlorella sp (Dirbaz & Roosta, 2018) had been studied . However, the proper lead metal adsorption isotherm model has not been studied to determine the adsorption capacity of the use of chitosan and coffee grounds adsorbents in reducing lead concentrations in industrial wastewater (Nurhidayanti et al, 2021; . The purpose of this study was to study the maximum adsorption capacity through an isotherm model, to determine the rate of adsorption kinetics in the use of chitosan and coffee grounds adsorbents in reducing lead concentrations in industrial wastewater and to study its thermodynamic magnitude.…”
Section: Introductionmentioning
confidence: 99%